Characteristics of the Approximate-Optimal Training Indicators of Goalkeepers in Modern Football - Doroshenko, I.; Svatyev, A.; Shamardin, V.; Khorkavyy, B.; Vaniuk, D. V.; Doroshenko, E. Yu.; Дорошенко, І.; Сватєв, А.; Шамардін, В.; Хоркавий, Б.; Ванюк, Дар'я Валеріївна; Дорошенко, Едуард Юрійович (My University, 2024)
Objectives. Is to systematize data on determining approximate and optimal indicators of training activities of goalkeepers in football at different stages of sports improvement in order to improve their training. Material and methods. 14 athletes who are training at MFC “Metalurg” (Zaporizhzhya), playing the role – of goalkeeper: 3 athletes – MFC “Metalurg” (Zaporizhzhya), 3 athletes – MFC “Metalurg, U-19” (Zaporizhzhya), 2 athletes – MFC “Metalurg, U-17” (Zaporizhzhya), 2 athletes – MFC “Metalurg, U-16” (Zaporizhzhya), 2 athletes – MFC “Metalurg, U-15” (Zaporizhzhya), 2 athletes – MFC “Metalurg, U-14” (Zaporizhzhya). Age range: 14-24. Term of preparatory training period: 01.08.2024 – 24.11.2024. Methods of research. Analysis and systematization of data from scientific literature and the resource of global information system “Internet”; pedagogical observations; analysis of video materials of training sessions and the competitive process, generalization of pedagogical experience and systematization of scientific data; pedagogical observations, analysis and evaluation of indicators of training and competitive activities of football players – goalkeepers; methods of mathematical statistics. Results. Analysis of the competitive activity of qualified goalkeepers allows us to state that the average goalkeeper in modern football – a participant in the latest world and European championships, UEFA tournaments has the following anthropometric parameters: height – 195 ± 2 cm; weight – 90 ± 2 kg; weight-height index – 0.45 ± 0.01 c.u. The analysis of the data contained allows us to state the presence of certain relationships between the indicators of morphometry and the level of development of motor abilities of football players of various playing roles with the indicators of the effectiveness and efficiency of their competitive activities: goalkeepers show reduced correlations with endurance development; flank defender and midfielder have reduced indicators of the relationship between the effectiveness of competitive activity and morphometric indicators and manifestations of flexibility. Conclusions. The results of experimental studies allow us to state that in the process of long-term sports training of football goalkeepers, the most significant psychological characteristics of the individual are: a high level of motivation to achieve the set goals, hard work, determination and psychological stability in the process of training sessions and competitive activities. In addition, the following indicators are critically important for the high-quality training of goalkeepers for professional football teams: morphometric parameters (height, limb length, weight, limb structure, muscle structure and ligament-articular apparatus), the level of development of leading motor abilities, manifestations of anticipatory reaction and subjective forecasting (anticipation of the flight of the ball, the moment and direction of the blow, the development of the game situation), physical fitness (general and special) and the pace of learning specific motor and technical-tactical actions of the goalkeeper. Матеріал і методи. 14 спортсменів, які тренуються в МФК «Металург» (Запоріжжя), амплуа – воротар: 3 спортсмени – МФК «Металург» (Запоріжжя), 3 спортсмени – МФК «Металург, U-19» (Запоріжжя), 2 спортсмени – МФК « Металург, U-17» (Запоріжжя), 2 спортсмени – МФК «Металург, U-16» (м. Запоріжжя), 2 спортсмени – МФК «Металург, U-15» (м. Запоріжжя), 2 спортсмени – МФК «Металург, U-14» (м. Запоріжжя). Віковий діапазон: 14-24. Термін підготовчого періоду навчання: 01.08.2024 – 24.11.2024. Методи дослідження: Аналіз та систематизація даних наукової літератури та ресурсів глобальної інформаційної системи «Інтернет»; педагогічні спостереження; аналіз відеоматеріалів навчально-тренувальних занять та змагального процесу, узагальнення педагогічного досвіду та систематизація наукових даних; педагогічні спостереження, аналіз та оцінка показників навчально-тренувальної та змагальної діяльності футболістів – воротарів; методи математичної статистики. Результати. Аналіз змагальної діяльності кваліфікованих воротарів дозволяє стверджувати, що середньостатистичний воротар сучасного футболу – учасник останніх чемпіонатів Європи і світу, турнірів UEFA має такі морфометричні параметри: зріст – 195 ± 2 см; вага – 90 ± 2 кг; масо-зростовий індекс – 0,45 ± 0,01 у.о. Аналіз наведених даних дозволяє констатувати наявність певних взаємозв’язків між показниками морфометрії та рівнем розвитку рухових здібностей футболістів різного ігрового амплуа з показниками результативності та ефективності їх змагальної діяльності: воротарі мають знижені кореляції з розвитком витривалості; у флангових захисників і півзахисників – знижені показники зв’язку ефективності змагальної діяльності з морфометричними показниками і проявами гнучкості. Висновок. Результати експериментальних досліджень дозволяють стверджувати, що в процесі багаторічної спортивної підготовки футбольних воротарів найбільш значущими психологічними характеристиками особистості є: високий рівень мотивації досягнення поставлених цілей, працьовитість, цілеспрямованість і психологічна активність. стійкість у процесі тренувальних занять і змагальної діяльності. Крім того, критично важливими для якісної підготовки воротарів для професійних футбольних команд є такі показники: морфометричні параметри (зріст, довжина кінцівки, вага, будова кінцівки, структура м’язів та зв’язково-суглобового апарату), рівень розвитку провідних рухові здібності, прояви випереджаючої реакції та суб’єктивного прогнозування (передбачення польоту м’яча, моменту та напрямку удару, розвитку ігрової ситуації), фіз. підготовленість (загальна і спеціальна) і темп навчання конкретним руховим і техніко-тактичним діям воротаря.
Характеристика орієнтовано-оптимальних тренувальних показників воротарів у сучасному футболі
Keywords: football; training indicators; characteristics; goalkeeper; sports preparation; футбол; тренувальні індикатори; характеристика; воротар; спортивна підготовка